Monodisperse silver powder and preparation method and application thereof

By preparing and optimizing the particle size distribution of silver powder, combined with specific preparation methods, the problem of poor uniformity of conductive film caused by the particle size distribution width of silver powder is solved, and high-density and fine-linear conductive patterns and electrode production are achieved, thereby improving the conductivity and line pass rate.

CN119159071AActive Publication Date: 2024-12-20ENOVATE3D (HANGZHOU) TECH DEV CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411653169.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-20
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the prior art, the particle size distribution of silver powder is relatively wide, and it is difficult to meet the requirements of high density and fine line production, resulting in poor uniformity of the thickness and thickness of the conductive film, affecting the conductivity.

Method used

By preparing monodispersed silver powder, the particle size distribution width of its D90, D50 and D10 particle size is within the range of 0.45~1, combined with specific preparation methods, including proportional control of mixed silver salt, ammonia water, reducing agent and surfactant, and reaction The feeding sequence and rate of liquid ensure uniformity and dispersion of the particle size distribution of silver powder.

Benefits of technology

The particle size distribution of silver powder is narrow and the uniformity of particle size distribution is achieved, which meets the requirements of high density of conductive patterns and fine lineization of electrodes, improves the line pass rate and reduces line width fluctuations, and forms a conductive film with good conductivity. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159071A_ABST
    Figure CN119159071A_ABST
Patent Text Reader

Abstract

The invention discloses monodisperse silver powder and a preparation method and application thereof, and relates to the technical field of metal conductive powder. And the D90 particle size, the D50 particle size and the D10 particle size of the monodisperse silver powder meet the following formula: X = (D90-D10) / D50, wherein X is 0.45-1. The particle size distribution width of the silver powder is limited, so that the particle size distribution of the silver powder is narrow, the uniformity of the particle size distribution is high, slurry formed subsequently can be uniformly dispersed, the manufacturing requirements of high density of conductive patterns and thinning of electrodes can be met, and a conductive film with good conductivity can be formed easily.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal conductive powders, and in particular to monodisperse silver powder and a preparation method and application thereof. Background Art

[0002] Silver powder is widely used in the photovoltaic field due to its excellent conductivity and oxidation resistance. It is usually mixed with glass powder to form a silver paste, which is then coated or printed on the electrode or circuit of the substrate, and then heated or calcined to sinter the silver particles to form a conductive film on the electrode or circuit, and an electrical connection is formed through the connection of the silver powder. However, the current conductive film has poor uniformity in thickness and thickness, which in turn affects its conductivity and cannot meet the production requirements of high-density conductive patterns and thin-line electrodes brought about by the reduction in the size of electronic components. Summary of the invention

[0003] The main purpose of the present invention is to provide a monodisperse silver powder and a preparation method and application thereof, so as to solve the problem that the silver powder in the prior art has a wide particle size distribution and is difficult to meet the requirements of high-density and fine-line production.

[0004] In order to achieve the above object, according to one aspect of the present invention, a monodisperse silver powder is provided, wherein the D90 particle size, D50 particle size and D10 particle size of the silver powder satisfy: X=(D90-D10) / D50, and X is 0.45-1.

[0005] Furthermore, the D50 particle size of the monodisperse silver powder is 100 nm to 5 μm, the D90 particle size is 300 nm to 5 μm, and the D10 particle size is 90 nm to 500 nm.

[0006] Furthermore, the tap density of monodisperse silver powder is 4~6g / cm 3 .

[0007] According to a second aspect of the present invention, there is provided a method for preparing monodisperse silver powder, comprising the following steps:

[0008] S1, mixing a first silver salt, a first ammonia solution, a first reducing agent and water to obtain a silver core solution;

[0009] S2, mixing the silver core solution, the first dispersant and the first solvent to obtain a first reaction solution;

[0010] S3, mixing a second silver salt, a second ammonia water, a surfactant and a second solvent to obtain a second reaction solution;

[0011] S4, mixing the second reducing agent, the second dispersing agent and the third solvent to obtain a third reaction solution;

[0012] S5, adding the second reaction liquid and the third reaction liquid to the first reaction liquid at the same rate to obtain a reaction liquid; wherein the first rate is equal to the second rate;

[0013] S6, filtering, washing and drying the reaction liquid in sequence to obtain silver powder.

[0014] Furthermore, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 1% / min to 40% / min of the reaction liquid volume.

[0015] Furthermore, the first silver salt, the first ammonia NH 3 , the molar ratio of the first reducing agent is (0.1-1): (0.1-5): (1-5); and / or, the molar ratio of the first silver salt to the first dispersant is (5-50): (0.05-1); and / or, the second silver salt, the second ammonia NH 3 , the molar ratio of the surfactant, the second reducing agent, and the second dispersant is (2.4~24):(2.4~120):(0.1~1):(24~120):(0.001~0.01); and / or the molar ratio of the first silver salt to the second silver salt is (0.005~0.5):1.

[0016] Furthermore, the concentration of the first dispersant in the first reaction solution is 0.25×10 -4 ~1.25×10 -2 mol / L; and / or, the concentration of the second silver salt in the second reaction solution is 0.06-1.20 mol / L; and / or, the concentration of the surfactant in the second reaction solution is 0.2×10 -3 ~0.12mol / L; and / or, the concentration of the second reducing agent in the third reaction solution is 0.6~3.0mol / L; and / or, the concentration of the second dispersant in the third reaction solution is 0.25×10 -4 ~1.25×10 -2 mol / L.

[0017] Further, the first silver salt and the second silver salt are each independently selected from at least one of silver nitrate, silver carbonate, silver oxalate, silver nitrite, silver chlorate, silver acetate, silver propionate, silver butyrate, silver lactate, silver bromide, silver chloride, and silver citrate; and / or, the first reducing agent and the second reducing agent are each independently selected from at least one of glucose, ascorbic acid, formaldehyde, hydrazine hydrate, sodium borohydride, sodium hypophosphite, hypophosphorous acid, citric acid, formic acid, and hydrazine hydrate; and / or, the first dispersant and the second dispersant are each independently selected from at least one of polyvinylpyrrolidone K1 0. At least one of polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K90, polyethylene glycol, polyacrylic acid, polyvinyl alcohol, gelatin, and gum arabic; and / or, the surfactant is selected from at least one of polyoxyethylene stearate-30, polyoxyethylene stearate-40, triethanolamine oleate, sorbitan laurate, polyoxyethylene lauryl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan stearate.

[0018] Further, the first solvent is selected from water or an alcohol solvent, and the alcohol solvent includes at least one of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, sec-butanol, amyl alcohol, isopentanol, β-phenylethanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol monomethyl ether; and / or, the second solvent and the third solvent are each independently a diol solvent, and the diol solvent includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,6-hexanediol, diethylene glycol, and dipropylene glycol.

[0019] Preferably, the first silver salt and the second silver salt are silver nitrate respectively; the first reducing agent and the second reducing agent are glucose respectively; the first dispersant and the second dispersant are polyvinyl alcohol respectively; the first solvent is water; the surfactant is polyoxyethylene lauryl ether; the second solvent and the third solvent are ethylene glycol respectively.

[0020] Further, in S6, the reaction liquid is filtered and the solid phase is collected; the solid phase is washed with a fourth solvent, wherein the fourth solvent is selected from at least one of water, methanol, ethanol, isopropanol, ether, ethyl acetate, propylene oxide, hexane, toluene, xylene, styrene, chloroform, acetone, and methyl butyl ketone; and / or the drying temperature is 45~85°C and the time is ≥10 h.

[0021] According to a third aspect of the present invention, a conductive silver paste is provided, and the conductive silver paste comprises the silver powder provided by the first aspect or the silver powder prepared by the preparation method provided by the second aspect.

[0022] Furthermore, the conductive silver paste can be used for the processing of metal wires ≥1μm, the printed line width fluctuation is <5%, and the printed line qualification rate is ≥99.0%.

[0023] According to a fourth aspect of the present invention, there is provided a conductive film, wherein the conductive film is prepared by treating the conductive silver paste of the third aspect with ≥150 o The conductive film is dried at a temperature of C, and the resistivity of the conductive film is ≤0.5 mΩ·mm.

[0024] The implementation of the present invention has at least the following beneficial effects:

[0025] The silver powder provided by the present invention has a narrow particle size distribution and high uniformity of particle size distribution by limiting the range of the particle size distribution width X, and can be evenly dispersed in the subsequent slurry formation, which can meet the production requirements of high-density conductive patterns and thin-line electrodes, improve the line qualification rate and reduce line width fluctuations, and help form a conductive film with good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a SEM image of the silver powder in Example 1 of the present invention;

[0027] Figure 2 This is the SEM image of the silver powder in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0029] The prior art has the problem that the silver powder has a wide particle size distribution. In order to solve the above problem, the first aspect of the present invention provides a monodisperse silver powder, wherein the D90 particle size, D50 particle size and D10 particle size of the monodisperse silver powder satisfy: X = (D90-D10) / D50, and X is 0.45-1.

[0030] In the present invention, D10 particle size is the particle size corresponding to when the volume cumulative distribution percentage of the sample reaches 10%, D50 particle size is the particle size corresponding to when the volume cumulative distribution percentage of the sample reaches 50%, and D90 particle size is the particle size corresponding to when the volume cumulative distribution percentage of the sample reaches 90%. The particle size distribution width SPAN value is recorded as X and is calculated according to the formula (D90-D10) / D50.

[0031] X is 0.45 to 1, for example, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 1 or any two thereof. By limiting the particle size distribution width SPAN value of the silver powder to a suitable range, the particle size distribution width is more concentrated, the narrower the particle size distribution range, the more uniform the particle size distribution.

[0032] The particle size distribution width range of the silver powder is related to the qualified rate and line width fluctuation of the circuit formed by the slurry formed by it during the application process. If the particle size distribution width range is wide, it is easy to cause breakpoints in the product pattern during the screen printing process. The particle size distribution width range of the silver powder is related to the dispersibility of the slurry formed by it, the density and width of the circuit, and the conductivity of the conductive film. If the particle size distribution width range is wide, it is easy to cause breakpoints in the product pattern during the screen printing process, the qualified rate of the circuit is low, and the line width fluctuation is large. During the sintering process, large holes will appear, resulting in large contact resistance, affecting conductivity. The present invention limits the particle size distribution width within the above range, so that the particle size distribution of the silver powder is narrower and the particle size distribution uniformity is high, which helps to improve its dispersibility in the slurry, can meet the requirements of high density of conductive patterns and thin lines of electrodes, and form a conductive film with good conductivity.

[0033] According to the research of the present invention, by limiting the width of its particle size distribution, the silver powder particle size distribution is narrow and the particle size distribution is highly uniform. It can be evenly dispersed in the subsequent slurry formation, which can meet the requirements of high density of conductive patterns and thin lines of electrodes, and also help to form a conductive film with good conductivity.

[0034] The D50 particle size of the monodisperse silver powder is related to the density of the formed conductive pattern and the thickness of the electrode. In some embodiments, D50 is 100nm~5μm. The present invention limits the D50 particle size of the monodisperse silver powder to 100nm~5μm, that is, the average particle size of the monodisperse silver powder is 100nm~5μm, and the average particle size is suitable, which can meet the production requirements of conductive patterns or electrodes of different thicknesses and thicknesses. The present invention limits the D50 particle size to 100nm~5μm, and can select silver powders with different D50 particle sizes according to actual needs, so as to realize the production of conductive patterns with different densities and electrodes with different thicknesses, and in particular, can realize the production of high-density conductive patterns and thin-line electrodes. Preferably, D50 is 120nm~2μm, that is, the D50 particle size of the silver powder is 120nm~2000nm, for example, 120nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1500nm, 2000nm or a range consisting of any two of them.

[0035] In some embodiments, the D90 particle size of the monodisperse silver powder is 300nm~5μm, and the D10 particle size is 90nm~500nm, such as 90nm, 100nm, 120nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, or a range consisting of any two thereof. Preferably, the D90 particle size of the monodisperse silver powder is 300nm~2.5μm, such as 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1500nm, 2000nm, 2500nm, or a range consisting of any two thereof.

[0036] The larger the tap density of the powder particles, the less likely they are to agglomerate. In some embodiments, the tap density of the monodisperse silver powder is 4-6 g / cm 3 , preferably 4.6~5.2g / cm 3 By limiting the tap density of the monodisperse silver powder within the above range, it is ensured that the silver powder does not agglomerate and has good dispersibility, which is conducive to improving the dispersibility of the slurry formed therefrom.

[0037] A second aspect of the present invention provides a method for preparing monodisperse silver powder, comprising the following steps:

[0038] S1, mixing a first silver salt, a first ammonia solution, a first reducing agent and water to obtain a silver core solution;

[0039] S2, mixing the silver core solution, the first dispersant and the first solvent to obtain a first reaction solution;

[0040] S3, mixing a second silver salt, a second ammonia water, a surfactant and a second solvent to obtain a second reaction solution;

[0041] S4, mixing the second reducing agent, the second dispersing agent and the third solvent to obtain a third reaction solution;

[0042] S5, adding the second reaction liquid and the third reaction liquid to the first reaction liquid at the same rate to obtain a reaction liquid;

[0043] S6, filtering, washing and drying the reaction liquid in sequence to obtain silver powder.

[0044] In the prior art, silver powder is mostly obtained by dropping a reducing agent into a silver precursor solution, or by mixing a reducing agent with a silver precursor solution at one time. In these methods, silver salt reduction, nucleation and growth are carried out simultaneously. Among them, the method of obtaining silver powder by dropping a reducing agent into a silver precursor solution, due to the high concentration of silver salt in the initial stage of the reaction, the addition of the reducing agent easily causes local agglomeration and growth of silver element particles, and the final particles are usually large in size, irregular in shape, and uneven in particle size distribution. The surface fails to effectively cover the dispersant ligand, which has a great influence on the dispersibility and stability of the conductive silver paste; and the method of obtaining silver powder by mixing a reducing agent with a silver precursor solution at one time, due to its too fast initial reaction speed, it will lead to uneven particle size distribution and poor particle morphology, which is not conducive to the dispersion uniformity of the conductive silver paste. The preparation method of the silver powder provided by the present invention can control the growth of silver by controlling the parameters such as the feeding sequence and the feeding speed, and by a method of first nucleation and then synchronous reduction growth, so as to control the morphology, particle size and dispersibility of the silver powder, and obtain silver powder with uniform and controllable particle size, good dispersibility and few surface impurities, and the reaction is mild and the yield is high, so that mass production can be realized.

[0045] The agglomeration of ultrafine powders is mainly caused by the mutual attraction between particles, so to reduce the agglomeration, the repulsion between particles must be increased. The present invention introduces a surfactant into the preparation system, wherein the surfactant can be adsorbed on the surface of the particles, and provides repulsion through electrostatic repulsion or by means of steric hindrance, such as the surfactant coating on the surface of the newly generated particles to act as a coating film to isolate the particles from each other, or the ionic surfactant makes the particles have the same charge, repel each other, inhibit the occurrence of agglomeration, and thus play a dispersing role; this coating can also inhibit the growth of particles, that is, control the size and morphology of the particles. In addition, the agglomerates in the reaction solution will produce microcracks that are easily healed by their own molecular forces under the action of mechanical forces, and the surfactant molecules can also automatically penetrate into the microcracks or adsorb on the crack walls to make the microcracks unable to heal, and the cracks are enlarged or the agglomerates are split into fragments by external forces. The present invention introduces a surfactant into the preparation process of ultrafine powders to act as a protective agent or dispersant, and under the mutual cooperation between the steps, it helps to prepare silver powder particles with good dispersibility and narrow particle size distribution.

[0046] Specifically, in S1, a first silver salt can be mixed with a first portion of water, and the silver salt (e.g., silver nitrate AgNO 3 ) will dissolve in water to form silver ions and obtain a silver salt solution; the first ammonia water is mixed with the second part of water to form an ammonia solution; a reducing agent (such as glucose, formaldehyde, etc.) is mixed with the third part of water to form a reducing agent solution; then the ammonia solution is added to the silver salt solution, and the ammonia water reacts with the silver ions to form a silver ammonia complex ([Ag(NH 3 )2 ] + ); adding a reducing agent solution thereto, the reducing agent will undergo an oxidation-reduction reaction with the silver ammonia complex to reduce the silver ions to silver atoms; the silver atoms form silver nuclei in the solution to obtain a silver nucleus solution. The concentration of the first silver salt in the silver salt solution is 0.0006-0.06 mol / L, and the concentration of the first reducing agent in the reducing agent solution is 0.03-0.3 mol / L.

[0047] In the preparation method of the present invention, the first reaction liquid is a mother liquid, the second reaction liquid is a silver ion solution containing a surfactant, and the third reaction liquid is a solution of a reducing agent with a reducing agent as the main body. In S1, the first silver salt is reacted with ammonia water and the first reducing agent to form a silver core, which is then formed into the first reaction liquid. At this time, the first reaction liquid is the mother liquid, and the second reaction liquid and the third reaction liquid in S3 and S4 are added to the first reaction liquid at the same rate. At this time, the second silver salt in the second reaction liquid is reduced to silver atoms under the action of the reducing agent and grows on the silver core at the same time. Through the preliminary nucleation process of S1, the number of nucleations in the initial stage can be effectively controlled, and the size uniformity during the growth process can be effectively controlled by subsequently dropping at the same rate.

[0048] The present invention does not limit the specific numerical value of S5 rate. For example, in some embodiments, the second reaction solution and the third reaction solution are respectively added to the first reaction solution at a rate of 1% / min~40% / min of the reaction solution volume. It can be understood that every 100 parts of the second reaction solution are added to the first reaction solution at a rate of 1 part / min~40 parts / min. Similarly, every 100 parts of the third reaction solution are added to the first reaction solution at a rate of 1 part / min~40 parts / min. Further, every 1000 parts of the second reaction solution are added to the first reaction solution at a rate of 10 parts / min~400 parts / min. Similarly, every 1000 parts of the third reaction solution are added to the first reaction solution at a rate of 10 parts / min~400 parts / min, and so on. By controlling the rate within the above range, different batches of D50 particle size silver powder can be prepared.

[0049] Specifically, the second reaction liquid and the third reaction liquid are respectively added to the first reaction liquid at a rate of 1% / min to 40% / min by volume of the reaction liquid. It can be understood that the addition rate of the second reaction liquid and the third reaction liquid is 1% / min to 40% / min by volume of the reaction liquid, for example, 1% / min, 2% / min, 5% / min, 10% / min, 20% / min, 30% / min, 40% / min or a range consisting of any two of them.

[0050] By controlling the amount of each raw material added, the D50 particle size of the silver powder can be effectively controlled.3 , the molar ratio of the first reducing agent is (0.1-1): (0.1-5): (1-5); and / or, the molar ratio of the first silver salt to the first dispersant is (5-50): (0.05-1); and / or, the second silver salt, the second ammonia NH 3 , the molar ratio of the surfactant, the second reducing agent, and the second dispersing agent is (2.4~24):(2.4~120):(0.1~1):(24~120):(0.001~0.01); and / or the molar ratio of the first silver salt to the second silver salt is (0.005~0.5):1, for example, 0.005:1, 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or a range consisting of any two of them.

[0051] By adjusting the concentration of substances in each reaction solution, the reaction rate can be effectively increased. For example, in some embodiments, the concentration of the first dispersant in the first reaction solution is 0.25×10 -4 ~1.25×10 -2 mol / L; and / or, the concentration of the second silver salt in the second reaction solution is 0.06-1.20 mol / L; and / or, the concentration of the surfactant in the second reaction solution is 0.2×10 -3 ~0.12mol / L; and / or, the concentration of the second reducing agent in the third reaction solution is 0.6~3.0mol / L; and / or, the concentration of the second dispersant in the third reaction solution is 0.25×10 -4 ~1.25×10 -2 mol / L.

[0052] The present invention does not limit the specific types of each raw material, and can be adjusted according to actual needs. For example, in some embodiments, the first silver salt and the second silver salt are each independently selected from at least one of silver nitrate, silver carbonate, silver oxalate, silver nitrite, silver chlorate, silver acetate, silver propionate, silver butyrate, silver lactate, silver bromide, silver chloride, and silver citrate; and / or, the first reducing agent and the second reducing agent are each independently selected from at least one of glucose, ascorbic acid, formaldehyde, hydrazine hydrate, sodium borohydride, sodium hypophosphite, hypophosphorous acid, citric acid, formic acid, and hydrazine hydrate; and / or, the dispersant is selected from at least one of polyvinyl pyrrolidone K10, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K90, polyethylene glycol, polyacrylic acid, polyvinyl alcohol, gelatin, and gum arabic; and / or, the first solvent is selected from water or an alcohol solvent, and the alcohol solvent includes methanol, ethanol, propanol, isopropanol, butyric acid, and the like. The surfactant is selected from at least one of polyoxyethylene stearate-30, polyoxyethylene stearate-40, triethanolamine oleate, sorbitan laurate, polyoxyethylene lauryl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan stearate; the second solvent and the third solvent are each independently selected from a diol solvent, and the diol solvent includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,6-hexanediol, diethylene glycol, and dipropylene glycol.

[0053] In S6, the reaction liquid is filtered and the solid phase is collected; the solid phase is washed with a fourth solvent, wherein the fourth solvent is selected from at least one of water, methanol, ethanol, isopropanol, ether, ethyl acetate, propylene oxide, hexane, toluene, xylene, styrene, chloroform, acetone, and methyl butyl ketone; and / or the drying temperature is 45-85°C, and the time is ≥10h, preferably 10-14h. The reaction liquid is filtered, the silver precipitate is separated from the solution, the solid phase is collected, the solid phase is washed with a fourth solvent to remove residual surfactants and dispersants, and then centrifuged, and the product after centrifugation is dried and ground to obtain silver powder.

[0054] Preferably, the first silver salt and the second silver salt are silver nitrate, the first reducing agent and the second reducing agent are glucose, the first dispersant and the second dispersant are polyvinyl alcohol, the first solvent is water, the surfactant is polyoxyethylene lauryl ether, and the second solvent and the third solvent are ethylene glycol. By limiting the above preparation parameters, the optimal performance can be improved.

[0055] A third aspect of the present invention provides a conductive silver paste, which comprises the silver powder provided by the first aspect or the silver powder prepared by the preparation method provided by the second aspect.

[0056] Since the silver powder with uniform particle size is included, the conductive silver paste has the advantages of high dispersibility, high uniformity and less agglomeration. If the silver powder in the conductive silver paste is unevenly dispersed, the silver powder is very likely to agglomerate, and the silver powder settles in the conductive silver paste to form an uneven conductive silver paste. When such a conductive silver paste is used to form a wiring layer and an electrode, the silver powder is unevenly present in the wiring layer and the electrode, resulting in a part where the silver powder does not exist locally, and a conductive film with good conductivity cannot be formed. Since the silver powder with narrow particle size distribution is included, the silver powder with narrow particle size distribution can be evenly dispersed in the paste, and a conductive film with uniform thickness, uniform thickness and good conductivity can be formed, and the line qualification rate is high and the line width fluctuation is low.

[0057] In one embodiment of the present invention, the silver powder can be mixed with an organic polymer to form a conductive silver paste, which can be dried or cured to form a film; in another embodiment of the present invention, the silver powder can be mixed with a glass powder to form a conductive silver paste, which can be directly sintered to form a film. Due to the inclusion of the silver powder, the conductive silver paste can particularly meet the production requirements of high-density conductive patterns and thin-line electrodes, and the formed conductive film has good conductivity.

[0058] In some embodiments, the above-mentioned conductive silver paste can be used for processing metal wires with a diameter of ≥1 μm, the printed line width fluctuation is <5%, and the printed line qualification rate is ≥99.0%.

[0059] A fourth aspect of the present invention provides a conductive film, wherein the conductive film is prepared by treating the conductive silver paste of the third aspect with ≥150 o C temperature drying.

[0060] Due to the inclusion of the above conductive silver paste, the conductive film has the advantages of high stability, low resistivity, good conductivity, etc. In some embodiments, the resistivity of the conductive film is ≤0.5 mΩ·mm.

[0061] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0062] Example 1

[0063] The method for preparing the silver powder of this embodiment comprises the following steps:

[0064] S1, 0.05g silver nitrate, 0.08g ammonia water, 0.2g glucose and 10mL water were mixed to obtain a silver core solution; wherein silver nitrate, NH 3, the molar ratio of glucose is 0.295:1.173:1.109;

[0065] S2, mixing the silver core solution, 0.25 g of polyvinyl alcohol (molecular weight 75000) and 100 mL to obtain a first reaction solution; the molar ratio of silver nitrate in S1 to polyvinyl alcohol in S2 is 44.3:0.5;

[0066] S3, 5 g of silver nitrate, 8 g of ammonia water, 0.5 g of polyoxyethylene lauryl ether (molecular weight 709) and 50 mL of ethylene glycol are mixed to obtain a second reaction solution; the molar ratio of the silver nitrate in S1 to the silver nitrate in S3 is 0.01:1;

[0067] S4, 20g glucose, 0.25g polyvinyl alcohol and 50mL ethylene glycol were mixed to obtain a third reaction solution; wherein the silver nitrate and NH4 in ammonia water in S3 and S4 were 3 , polyoxyethylene lauryl ether, glucose, and polyvinyl alcohol have a molar ratio of 8.81: 35.23: 0.212: 33.28: 0.001;

[0068] S5, adding the second reaction liquid and the third reaction liquid to the first reaction liquid at a rate of 0.5 mL / min, respectively, to obtain a reaction liquid;

[0069] S6, filtering the reaction liquid, collecting the solid phase, washing it with ethanol, drying it at 65° C. after centrifugation, and grinding it to obtain silver powder.

[0070] Example 2

[0071] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 1 mL / min respectively.

[0072] Example 3

[0073] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 5 mL / min respectively.

[0074] Example 4

[0075] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 10 mL / min respectively.

[0076] Example 5

[0077] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 20 mL / min respectively.

[0078] Example 6

[0079] The difference from Example 1 is that in S3, 0.5 g of polyoxyethylene lauryl ether is replaced by 0.25 g of polyoxyethylene lauryl ether, so that the silver nitrate and NH4OH in ammonia water in S3 and S4 are 3 The mass ratio of polyoxyethylene lauryl ether, glucose and polyvinyl alcohol is 8.81:35.23:0.106:33.28:0.001.

[0080] Example 7

[0081] The difference from Example 1 is that 20 g of glucose is replaced by 10 g of glucose in S4, so that the silver nitrate and NH4 in ammonia water in S3 and S4 are 3 The mass ratio of polyoxyethylene lauryl ether, glucose and polyvinyl alcohol is 8.81: 35.23: 0.212: 16.64: 0.001.

[0082] Example 8

[0083] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 0.1 mL / min respectively.

[0084] Example 9

[0085] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 30 mL / min respectively.

[0086] Comparative Example 1

[0087] The preparation method of the silver powder in this comparative example comprises the following steps:

[0088] S1, 5.05 g of silver nitrate, 8.08 g of ammonia water, 0.25 g of polyoxyethylene lauryl ether, 0.25 g of polyvinyl alcohol and 150 mL of water are mixed to obtain solution A;

[0089] S2, 20 g of glucose, 0.25 g of polyvinyl alcohol and 50 mL of ethylene glycol were mixed to obtain solution B;

[0090] S3, adding solution B to solution A, heating to 70° C., to obtain a reaction solution;

[0091] S4, filtering the reaction liquid, collecting the solid phase, washing it with ethanol, drying it at 65° C. after centrifugation, and grinding it to obtain the silver powder of this comparative example.

[0092] Comparative Example 2

[0093] The difference from Example 1 is that 0.5 g of polyoxyethylene lauryl ether is not added in S3, and ethanol is replaced by water in S4.

[0094] Comparative Example 3

[0095] The difference from Example 1 is that in S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at one time.

[0096] Test example

[0097] 1. Particle size test

[0098] Particle size observation: A Phenom scanning electron microscope was used to characterize the size and morphology of the silver powder. The specific operation was as follows: the silver powder was diluted in deionized water or an organic solvent at a mass ratio of 1:500 to obtain a dilution; the dilution was ultrasonically dispersed, a small amount was taken with a dropper and added to the surface of the silicon wafer and heated to remove the solvent; after the sample was prepared and sprayed with gold, the size and morphology image information of the silver powder was obtained under a Phenom scanning electron microscope, where the particle size distribution width SPAN was calculated according to the formula (D90-D10) / D50, D10 is the particle size corresponding to the cumulative volume distribution percentage of the sample reaching 10%, D50 is the particle size corresponding to the cumulative volume distribution percentage of the sample reaching 50%, and D90 is the particle size corresponding to the cumulative volume distribution percentage of the sample reaching 90%.

[0099] 2. Tap density test

[0100] Use a tap density meter to measure the tap density of powder: take an appropriate amount of silver powder and weigh it on an analytical balance to read the mass as m; put the silver powder into the measuring cylinder used by the tap density meter with the surface of the silver powder level. Place the measuring cylinder on the tap density meter and vibrate it with an amplitude of 3 mm and a vibration frequency of 200 times / min until the volume of the silver powder no longer decreases. Read the volume at this time as v; According to the tap density formula ρ=m / v, the tap density data of the silver powder is obtained.

[0101] 3. Print circuit test

[0102] Use a Nordson EFD dispenser to perform a slurry printing test: 17g of silver powder, 1g of polyurethane, 1g of isophorone and 1g of diethylene glycol butyl ether acetate are mixed to form a conductive slurry; the prepared conductive slurry is loaded into a 3mL material tube and equipped with a 25μm glass needle, the entire device is loaded into a booster pen, and connected to the dispenser; the pressure is adjusted to 20psi, each line is 100mm long and 40μm wide; 3mL of slurry is printed without any circuit breakage or blockage, and the pass rate is the number of qualified lines / total number of lines. If the pass rate is 99.0% or above, the performance test is passed, and if the pass rate is lower than 99.0%, it fails.

[0103] 4. Line width stability test

[0104] Use a microscope to read the line width data in the printed circuit test, randomly select 50 lines for line width test, measure the line width of each line at 3 different positions and take the average; if the width fluctuation of 50 lines is ≤5.0%, the printed circuit is stable, and if the width fluctuation is greater than 5.0%, it is unstable.

[0105] 5. Conductivity test

[0106] The resistivity of the slurry was tested using a Ruike Weiye FT-340 four-probe square resistance tester: the prepared conductive slurry was scraped onto the glass original plate by a coating machine, and sintered at 200°C for 1h in a nitrogen atmosphere to obtain a conductive film with a thickness of 15μm; the thickness of the conductive film sample after high-temperature sintering was measured with the help of a step meter; the corresponding parameters were set in the square resistance meter, and the four probes were adjusted to press down vertically above the sample and touch lightly; the resistivity data was recorded after the readings stabilized.

[0107] The test results are shown in Table 1.

[0108] Table 1

[0109]

[0110] according to Figure 1 It can be seen that the silver powder particles in Example 1 have uniform size, good dispersibility, and no obvious agglomeration. Figure 2 It can be seen that the silver powder in Comparative Example 1 has agglomeration phenomenon and poor dispersibility. According to Table 1, the preparation method of the present invention can effectively improve the uniformity of the silver powder particle size distribution, and the slurry formed by the silver powder can produce a conductive film with a resistivity of ≤0.5mΩ·mm, and further a conductive film with a resistivity of ≤0.27mΩ·mm, and the qualified rate of the circuit printed by the slurry is ≥99.1%, and the line width fluctuation is <5%, which can meet the production requirements of high density of conductive patterns and thin lines of electrodes brought about by the reduction in the size of electronic components.

[0111] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A monodisperse silver powder, characterized in that: The D90 particle size, D50 particle size and D10 particle size of the monodisperse silver powder satisfy the following conditions: X=(D90-D10) / D50, where X is 0.45-1.

2. The monodisperse silver powder according to claim 1, characterized in that: The D50 particle size of the monodisperse silver powder is 100nm~5μm, the D90 particle size is 300nm~5μm, and the D10 particle size is 90nm~500nm.

3. The monodisperse silver powder according to claim 1, characterized in that: The tap density of the monodisperse silver powder is 4-6 g / cm 3 .

4. A method for preparing the monodisperse silver powder according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing a first silver salt, a first ammonia solution, a first reducing agent and water to obtain a silver core solution; S2, mixing the silver core solution, the first dispersant and the first solvent to obtain a first reaction solution; S3, mixing a second silver salt, a second ammonia water, a surfactant and a second solvent to obtain a second reaction solution; S4, mixing the second reducing agent, the second dispersing agent and the third solvent to obtain a third reaction solution; S5, adding the second reaction liquid and the third reaction liquid to the first reaction liquid at the same rate to obtain a reaction liquid; S6, filtering, washing and drying the reaction liquid in sequence to obtain silver powder.

5. The preparation method according to claim 4, characterized in that: In step S5, the second reaction liquid and the third reaction liquid are added to the first reaction liquid at a rate of 1% / min to 40% / min of the reaction liquid volume.

6. The preparation method according to claim 4, characterized in that: The molar ratio of the first silver salt, NH3 in the first ammonia water, and the first reducing agent is (0.1-1): (0.1-5): (1-5); and / or, the molar ratio of the first silver salt to the first dispersant is (5-50): (0.05-1); and / or, the molar ratio of the second silver salt, NH3 in the second ammonia water, the surfactant, the second reducing agent, and the second dispersant is (2.4-24): (2.4-120): (0.1-1): (24-120): (0.001-0.01); and / or, the molar ratio of the first silver salt to the second silver salt is (0.005-0.5):

1.

7. The preparation method according to claim 4, characterized in that: The concentration of the first dispersant in the first reaction solution is 0.25×10 -4 ~1.25×10 -2 mol / L; and / or, the concentration of the second silver salt in the second reaction solution is 0.06-1.20 mol / L; and / or, the concentration of the surfactant in the second reaction solution is 0.2×10 -3 ~0.12mol / L; and / or, the concentration of the second reducing agent in the third reaction solution is 0.6~3.0mol / L; and / or, the concentration of the second dispersant in the third reaction solution is 0.25×10 -4 ~1.25×10 -2 mol / L.

8. The preparation method according to claim 4, characterized in that: The first silver salt and the second silver salt are each independently selected from at least one of silver nitrate, silver carbonate, silver oxalate, silver nitrite, silver chlorate, silver acetate, silver propionate, silver butyrate, silver lactate, silver bromide, silver chloride, and silver citrate; and / or, the first reducing agent and the second reducing agent are each independently selected from at least one of glucose, ascorbic acid, formaldehyde, hydrazine hydrate, sodium borohydride, sodium hypophosphite, hypophosphorous acid, citric acid, formic acid, and hydrazine hydrate; and / or, the first dispersant and the second dispersant are each independently selected from at least one of polyvinylpyrrolidone At least one of ketone K10, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K90, polyethylene glycol, polyacrylic acid, polyvinyl alcohol, gelatin, and gum arabic; and / or the surfactant is selected from at least one of polyoxyethylene stearate-30, polyoxyethylene stearate-40, triethanolamine oleate, sorbitan laurate, polyoxyethylene lauryl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan stearate.

9. The preparation method according to claim 4, characterized in that: The first solvent is selected from water or an alcohol solvent, and the alcohol solvent includes at least one of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, sec-butanol, amyl alcohol, isopentanol, β-phenylethanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol monomethyl ether; and / or the second solvent and the third solvent are each independently a diol solvent, and the diol solvent includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,6-hexanediol, diethylene glycol, and dipropylene glycol.

10. The preparation method according to claim 4, characterized in that: In step S6, the reaction liquid is filtered to collect the solid phase; the solid phase is washed with a fourth solvent, wherein the fourth solvent is selected from at least one of water, methanol, ethanol, isopropanol, ether, ethyl acetate, propylene oxide, hexane, toluene, xylene, styrene, chloroform, acetone, and methyl butyl ketone; and / or the drying temperature is 45-85° C. and the time is ≥10 h.

11. A conductive silver paste, characterized in that: The conductive silver paste comprises the silver powder according to any one of claims 1 to 3 or the silver powder prepared by the preparation method according to any one of claims 4 to 10.

12. The conductive silver paste according to claim 11, characterized in that: The conductive silver paste is used for processing metal wires with a diameter of ≥1 μm, the printed line width fluctuation is <5%, and the printed line qualification rate is ≥99.0%.

13. A conductive film, characterized in that: The conductive film is prepared by drying the conductive silver paste according to claim 11 or 12 at a temperature of ≥150° C., and the resistivity of the conductive film is ≤0.5 mΩ·mm.

Citation Information

Patent Citations

  • Preparation method of solar battery panel silver powder

    CN106583746A

  • Preparation method of high tap density and high-dispersion spherical silver powder

    CN110434355A

  • Sphere-like silver powder with particle size capable of being accurately controlled and preparation method thereof

    CN112475311A

  • Preparation method of silver powder for conductive paste

    CN112605394A

  • High-tap-density micron silver powder and preparation method thereof

    CN117753982A